Educational technologies for accident prevention due to falls in childhood: a scoping review - Abiúde Nadabe e Silva; Aline Costa de Oliveira; Jefferson Abraão Caetano Lira; Ana Roberta Vilarouca da Silva; Lídya Tolstenko Nogueira (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to map evidence on educational technology use for accident prevention due to falls in childhood. Methods: a scoping review, carried out in October and November 2022, in the MEDLINE, Web of Science, BDENF and CINAHL databases and LILACS bibliographic index. There was no delimitation of language or time. Data were extracted and analyzed descriptively by two independent researchers. The research protocol was registered in the Open Science Framework. Results: twenty-six studies were selected. Booklets, pamphlets and leaflets were the most used technologies, presenting health services as the most frequent environment to develop research on fall prevention. The technologies developed were important outcomes: increased knowledge of children, family members, caregivers, health and education professionals. Conclusions: educational technology use makes it possible to increase knowledge, adopt safe practices and reduce falls.